Congruence in advertising, how can communication deal with cultural diversity? The case of HSBC campaign - AOUN, Georges; DEL OLMO, Joseph Luis; BOURLIATAUX-LAJOINIE, Stephane (Proche-Orient Études en management, 2019)
Mass marketing which prevailed in the 20th Century is fading and is quickly being replaced by customized marketing as consumers are becoming more sophisticated and are now actively looking for companies that can satisfy their specific needs. It is clear that marketers in the 21st Century face many challenges: longer life expectancy and the increase in the number of seniors within the population, fast-paced development of technologies applied to communication and marketing, globalization which has led to the free movement of people, goods and services, the emergence of cultural factors in many markets. At the same time, these challenges provide new opportunities for marketers and generate certain impacts and influences on the whole field of marketing.